The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.37496/rbz5220210040
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of endocrine response of thyroid and intestinal and adipose tissues due to the addition of Moringa oleifera essential oil in diet for quails exposed to heat stress

Abstract: In this study, we aimed to determine the effect of Moringa oleifera essential oil (MOEO) supplementation to rations of Japanese quail (Coturnix coturnix japonica) grown under heat stress (HS) on some adipokine (visfatin, adiponectin, and chemerin), intestinal (citrulline), 3,5,3′-triiodothyronine (T3), thyroxine (T4), and thyroid-stimulation hormone (TSH) levels in the serum. For this purpose, 320 day-old male quail chicks were used. The study was conducted over 42 days, including a 7-d adaptation period and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Moreover, no adverse effects on growth performance or nutrient utilisation were observed. These findings are consistent with those of Bayraktar et al (2023), who reported decreased T4 concentrations when Moringa oleifera essential oil was incorporated into quail diets. Similarly, the use of feed additives such as genistein or sodium butyrate also reduced T4 concentrations (El-Maaty et al, 2023;Li et al, 2024).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, no adverse effects on growth performance or nutrient utilisation were observed. These findings are consistent with those of Bayraktar et al (2023), who reported decreased T4 concentrations when Moringa oleifera essential oil was incorporated into quail diets. Similarly, the use of feed additives such as genistein or sodium butyrate also reduced T4 concentrations (El-Maaty et al, 2023;Li et al, 2024).…”
Section: Discussionsupporting
confidence: 92%
“…Digestion and absorption of the consumed nutrients occur depending on the biochemical reactions that may alter according to the animal's breed, health status and The Effects of Hawthorn (Crataegus oxyacantha) Fruit Extract on Performance, Carcass and Some Serum Parameters of Broilers.... environmental factors (Bayraktar et al, 2023). Stress is an important factor that changes biochemical parameters (Kaya et al, 2021).…”
Section: Serum Parametersmentioning
confidence: 99%
“…According to the literature, phenolic acids, flavonoids, glucosinolates, isothiocyanates, sterols, and fatty acids are discovered in different parts of M. oleifera (Singh et al, 2020). Leaves are known to possess various biological attributes, including hypocholesterolemic, antidiabetic, and hypertensive properties (Abd Rani et al, 2018), regulate thyroid hormones (Bayraktar et al, 2023), the central nervous system (Su et al, 2023), digestive system (Wu et al, 2023), nutrition (Yang et al, 2023), and metabolic process of the eyes, ears, nose, throat, and the genitourinary system (Kumar and Karthik, 2023) to treat gastric ulcers (Islam et al, 2021) and scurvy (Rathore et al, 2023). Studies have described the plant as having very potent antiinflammatory and anti-tumor properties (Chaudhary et al, 2022).…”
Section: Introductionmentioning
confidence: 99%